(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
In modern conditions of management, the problem of forming an effective methodology for accounting credit banking operations is becoming more important. The purpose of the study is to substantiate the theoretical and methodological aspects of improving the organization of credit operations accounting at PJSC «State Savings Bank of Ukraine». Was been analyzed the approaches of scientists to the interpretation of the essence «credit operation», and was determined place in the system of related concepts. Was identified the organization of accounting of credit banking operations as a process covering the distribution of duties and credit powers in the course of operations is identified; description of procedures for performing credit operations and control over them. A model for lending to individuals and legal entities has been developed, which makes it possible to take into account all aspects of the organizational process of recording credit operations and to improve the quality of accounting procedures at PJSC «State savings bank of Ukraine». With the purpose of improving the organization of credit operations accounting, PJSC «State savings bank of Ukraine» was asked to introduce the practice of accounting for overdue accrued income for credit operations with transfer to sub-accounts in accordance with the period of non-repayment of debts. Such a bank’s organization of the process of recording credit operations will provide an efficient and flexible system for managing credit operations. The trust of creditors and depositors to banks will increase as a result of increasing stability, stability and competitiveness in the world market of the banking system of Ukraine, capable of meeting the needs of the population and the economy in loans and other banking services to the maximum and qualitatively